If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + -15 = -8x + 11 Reorder the terms: -15 + -9x = -8x + 11 Reorder the terms: -15 + -9x = 11 + -8x Solving -15 + -9x = 11 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -15 + -9x + 8x = 11 + -8x + 8x Combine like terms: -9x + 8x = -1x -15 + -1x = 11 + -8x + 8x Combine like terms: -8x + 8x = 0 -15 + -1x = 11 + 0 -15 + -1x = 11 Add '15' to each side of the equation. -15 + 15 + -1x = 11 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = 11 + 15 -1x = 11 + 15 Combine like terms: 11 + 15 = 26 -1x = 26 Divide each side by '-1'. x = -26 Simplifying x = -26
| -(3u-2x-3)= | | t/8-8=8 | | -18-3x=6-4x | | (-2+2v+2u)(-7)= | | -2*x+9=25 | | -2(r-6)=-37 | | 2*x+7=5 | | (y-15)-(1y-10)=19 | | 3(2x-5)-4(x-1)=(-3x-6)-3(x+3) | | 5*x+3=13 | | -9x-24=-11x+10 | | -6t=-39 | | log(x+15)-log(x)=0.65 | | 40x=18000+5y | | -47-91=156-9x | | -32-4x=46-x | | 2x-5=5-2 | | 5x-3(2x-10)=25 | | 34+03*2-25+5= | | z^2-(3+4i)z-1-5i=0 | | -46-(-28)= | | 78+n=3n-40 | | 5y-8=12x+4 | | 5y+24=y-8 | | 1.84g-8=0.28 | | 48=3.2x | | 4x+8-8x=32-4x | | 84+n=36-3n | | 3y-18=6 | | 7-1.5x=62.5 | | 4x-47=7x+22 | | 5+5+5+5+5=555 |